Quantitative approach of Min protein researches and applications: Experiments, mathematical modeling and computer simulations - Waipot Ngamsaad (2018)
Cell division in prokaryotes is a process (known as binary fission) where the parent cell divides into daughter cells. In this process, the dynamics of Min proteins is an important factor in the accurate positioning at the midcell in Escherichia coli. This site specificity is regulated by the oscillatory behavior of Min proteins. Numerous studies of Min protein dynamics have focused on dynamic spatial-temporal pattern formation, the movement mechanism and the biochemical basis function mostly using wet lab experiments, but the quantitative data remains limited. Thus in this research review, focus is on quantitative methodologies. Up-to-date information and findings regarding Min proteins, particularly MinD proteins obtained by using quantitative approaches such as experiments, modeling and simulations were provided. This review of quantitative techniques is expected to benefit not only those who want to conduct research in this area using more quantitative approaches, but also those who are interested in using qualitative data to support their findings. © 2009 Academic Journals.